The Philosophy of Islamic Education Views on Humans, Society and the Environment - Haryati, Aisyah; Fahmi, Faiz; Saripudin, Uus; Supardi, Edi (UNIVERSITAS PAKUAN, 2025)
The philosophy of Islamic Education is the mother of all knowledge that has developed from ancient Greece to modern times. The view of Islamic educational philosophy towards human beings is in accordance with its development period because the educational process in the principle of Islamic views is tarbiyah, meaning in accordance with human life habits. In the Qur'an, there are three concepts about the meaning of human beings, namely al-Basyar, al-Insan, and An-Nas. The first concept is al-Basyar, human beings should not be much different from other biological beings. Thus, human life is bound to other principles of biological life such as breeding, experiencing a phase of growth in reaching maturity and maturity. The second concept is al-Insan which is used in the Qur'an to show the totality of human beings as physical and spiritual beings. The harmonization of these two aspects with the various potentials they have can rely on humans as unique and special creatures of God. The third concept is that humans are created as social creatures starting from a male and female couple and then developing into tribes and nations to get to know each other. Then the view of Islamic philosophy towards society is that it is clear that Islam has regulated various things as well as education with all its aspects. Islamic education plays a very important role in determining the fate of a society because the Qur'an has been revealed since its inception aims to guide society to the truth. Furthermore, the view of Islamic education philosophy on the environment is that it must be active in utilizing it such as land, water, air, and so on.